Caffeine Intoxication in Pregnancy: Report of a case - Nojima, Tsuyoshi; Naito, Hiromichi; Kosaki, Yoshinori; Osako, Takaaki; Tanaka, Kimiaki; Murata, Atsuo; Nakao, Atsunori (Archives of Academic Emergency Medicine, 2019)
Although fatalities due to caffeine intoxication are uncommon,a caffeine overdose may cause profound toxicity, resulting in tachycardia, arrhythmia, convulsions, vomiting, coma, and possibly death. In particular, high caffeine consumption while pregnant can cause increased fetal catecholamine levels, which could lead to increased fetal heart rate and placental vasoconstriction and impair fetal oxygenation. Therefore, caffeine intoxication in pregnant women should be treated immediately. Herein, we present a 33-year-old pregnant woman who was treated in our department afteringesting 4000mg of caffeine in an attempt to commit suicide. We successfully treated our patient, and she delivered a healthy baby at 38 weeks. Â